Development of an HPLC/DAD method for determination of phenolic profile in portuguese olive fruits - Ferreira da Vinha, Ana (2001)
Phenolics are characteristic constituents of green plants occurring in virtually all parts of the plant but with quantitative distributions that vary between different organs of the plant and within different populations of the same plant species. Phenolics in olive pulp and oil constitute a complex mixture and the complete chemical nature has not, as yet, been elucidated1 Phenolic compounds may contribute to fruit quality in a number of ways; for example, by contributing to sensory attributes, such as colour and flavour, and through the contribution of some specific phenolics, in particular oleuropein, to the intense bitterness of the olive fruit. Factors contributing to the variability in phenolic distribution include cultivar and genetics, geographical origin, maturity, climate, position on tree, rootstock and agricultural practices. In the case of processed products, technological processes to which olive fruits are exposed may also impact significantly on the phenolic content. Here we studied the following aspects of the determination of polyphenols in Portuguese olive fruits: extraction, chromatographic separation, and quantification.